Strategies and responses to the effects of Climate Change on health systems in Sub-Saharan Africa: A scoping review protocol. - Chancy Skenard Chimatiro; Solange Mianda; Precious Hajison; Martina Lembani (PLoS ONE)
Background Climate change is recognized as the greatest global health threat of the 21st century. Projections suggest that the Sub-Saharan African region will face more consequences of climate change than any other region globally. The health systems within the region have been affected by the negative effects of climate change. Mapping strategies and responses used in the region to address the effects of climate change on health systems in Sub-Saharan Africa could be a starting point for understanding evidence-based decision-making to inform best practices. Methods This scoping review will follow the methodological framework by Arksey & O'Malley. A wide range of databases will be searched to identify articles published on the strategies and responses to the effects of climate change on the health systems in Sub-Saharan Africa. Only peer-reviewed articles (original quantitative and qualitative studies, mixed methods, systematic reviews, editorials, and commentaries) published in English Language between 2010 and 2024 will be reviewed. All Book chapters and the grey literature (dissertations, conference proceedings, abstracts, reports) and publications primarily focusing on climate change strategies and responses without effects on health systems will be excluded. Covidence software will be used during study selection, data extraction, and summary. Deductive thematic analysis will be performed using predetermined themes from the objectives. Dissemination The results of this scoping review will be disseminated at local and international research conferences. Furthermore, the findings will be published in open-access journals targeting different audiences. The findings will also be shared with the Ministry of Health in Malawi for possible policy considerations.